A comprehensive analysis of the acromial morphology and etiological factors of partial rotator cuff tears - Yukihiro Kajita, MD, PhD; Yohei Harada, MD, PhD; Ryosuke Takahashi, MD; Ryosuke Sagami, MD; Yusuke Iwahori, MD, PhD (JSES International)
Background: Rotator cuff tears are divided into complete and partial tears, and partial rotator cuff tears include articular-sided tears and bursal-sided tears. Tears are caused by extrinsic, intrinsic, or traumatic factors; however, the mechanisms by which partial tears occur remain unknown. Recent reports have described the correlation between acromial morphology and rotator cuff tears. To date, no reports have investigated acromial morphology in partial tears. The purpose of this study is to evaluate the incidence of abnormal acromial morphology in both partial articular-sided and bursal-sided rotator cuff tears. Methods: Patients with supraspinatus tendons that had articular-sided tears were categorized into Group A, and patients who had bursal-sided tears were categorized into Group B. Patients who underwent arthroscopic rotator cuff repair for rotator cuff tears were assessed based on their diagnosis of Group A or Group B according to arthroscopic findings. The following items were examined: age, sex, presence of diabetes mellitus, acromiohumeral distance (AHD), critical shoulder angle (CSA), lateral acromial angle (LAA), sagittal and coronal morphologies of the acromion, and traumatic shoulder tears. Results: There were 39 patients in Group A and 95 patients in Group B. A significantly greater rate of presence of diabetes was found in the Group A. There were no significant differences in age, sex, or frequency of traumatic shoulder tears. The mean AHD, CSA, and LAA in Group A and Group B were as follows: AHD, 9.4 ± 1.5 and 9.3 ± 1.4 mm; CSA, 32.1 ± 4.6 and 35.3 ± 4.4 degrees; LAA, 82.2 ± 7.2 and 79.9 ± 7.0 degrees. There were no significant differences between the groups. Although the CSA was significantly greater in Group B, there was no significant difference in the AHD or LAA. There was no significant difference in sagittal acromial morphology; however, Group B had significantly more inferior osteophytes of the acromial center in the coronal plane. Conclusion: Group B was found to have a significantly larger mean CSA compared to Group A. Group B occurred more often in patients with inferior osteophytes of the acromial center on the acromion, suggesting the involvement of extrinsic factors.